2005
DOI: 10.1093/eurheartj/ehi622
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic differences between different types of bundle branch block during the early phase of acute myocardial infarction: insights from the Hirulog and Early Reperfusion or Occlusion (HERO)-2 trial

Abstract: RBBB accompanying anterior AMI at presentation and new BBB (including LBBB) early after fibrinolytic therapy are independent predictors of high 30-day mortality. These electrocardiographic features should be considered in risk stratification to identify high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 25 publications
7
84
0
8
Order By: Relevance
“…8 All ECGs were sent to the core ECG laboratory at Green Lane Hospital, Auckland, New Zealand, for analysis. 2,8,12 Eight experienced ECG technicians screened all trial patients to identify those with any widening of the QRS on any of the paired ECGs. These ECGs were reviewed by a cardiologist (CKW) to identify the current cohort who had bundle-branch block at either of the 2 time points.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 All ECGs were sent to the core ECG laboratory at Green Lane Hospital, Auckland, New Zealand, for analysis. 2,8,12 Eight experienced ECG technicians screened all trial patients to identify those with any widening of the QRS on any of the paired ECGs. These ECGs were reviewed by a cardiologist (CKW) to identify the current cohort who had bundle-branch block at either of the 2 time points.…”
Section: Methodsmentioning
confidence: 99%
“…These ECGs were reviewed by a cardiologist (CKW) to identify the current cohort who had bundle-branch block at either of the 2 time points. 2 The present study was predefined before data lock. 2 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Escoteguy et al 19 in 1992 studied the bundle branch & AV block as complications of acute MI in thrombolytic era, and mean age of studied population was 59.9±15.2 years. Newby et al 13 Site of infarct :In our study blocks involving the BBB were more common in anterior infarction (table 7) but blocks at the atrioventricular node occurred predominantly in inferior infarction (table 13).…”
Section: Agementioning
confidence: 99%
“…In several studies on chronic and acute CAD, LBBB was found to be an excellent predictor of mortality and events [20][21][22][23][24] (Table 2). In 681 patients with acute myocardial infarction (AMI) enrolled in the Thrombolysis and Angioplasty in Myocardial Infarction (TAMI) 9 and Global Utilization of Streptokinase and t-PA for Occluded Arteries (GUSTO) 1 protocols, 25 the incidence of LBBB was found to be 7%.…”
Section: Left Bundle-branch Block and Risk Stratification In Heart DImentioning
confidence: 99%